Farmers' Motivation, Driving Factors and Inhibiting Factors in Clove Cultivation in North Kolaka District - Nurdiana (PT. Maju Malaqbi Makkarana, 2024)
Cloves have a significant role in economic development in Indonesia. The development of clove production and prices in Indonesia from 2003 - now fluctuates with a tendency to increase every year with an average growth rate of 1%. However, the price issue is the main problem in clove cultivation. This study aims to see how much the level of farmer motivation is related to clove cultivation and see the relationship between factors driving farmer motivation and the level of farmer motivation, and factors inhibiting farmer motivation and the level of motivation of farmers in North Kolaka Regency. This study used a qualitative approach by observing and interviewing farmers in North Kolaka district, while the number of informants in this study were 15 informants